Prediction of microscale rock mechanical performance from microCT images: Heterogeneous coal as an example - Zhang, Y.; Zhang, Z.; Sarmadivaleh, Mohammad; Lebedev, Maxim; Barifcani, Ahmed; Iglauer, Stefan (2017)
© 2017 ARMA, American Rock Mechanics Association. The prediction of rock mechanical performance is very important as it is directly related to safety issues and geological engineering design. However, there is a lack of understanding at the micrometer scale. Thus we introduce a new method to predict micro scale rock mechanical properties based on microCT imaging, combined with nanoindentation testing and discrete element method (DEM) modelling. Essentially microCT scanning and nanoindentation testing provide the morphology and mechanical property inputs for the DEM simulation. As an example the CO2-swelling effect of a highly heterogeneous coal sample is presented, and we were able to correctly predict the internal stresses, and the failure mechanisms of the unswelling (mineral) phase, consistent with lab experiments. We thus conclude that the proposed method can accurately and efficiently predict the rock mechanical performance at microscale.